EFEKTIVITAS MEDIA EDUKASI BERBASIS WHATSAPPBOT & CERAMAH TERHADAP PENINGKATAN PENGETAHUAN IBU TENTANG GASTROENTERITIS PADA ANAK - Nurcahyaningtyas, Widya; Cahya, Dea; Rifdah, Arini; Ariyanti, Lilis (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
The health education activity on efforts to prevent dengue fever with 4M plus given to housewives in Ngaban Village, Tanggulangin Sidoarjo is a form of community service activity in the form of delivering material on efforts to prevent dengue fever with 4M plus as a way to prevent the occurrence of dengue fever. Implementation of outreach activities on December 17 2023 at the Ngaban Village Hall, Tanggulangin Sidoarjo. The target of this health education activity is housewives in Ngaban Village, Tanggulangin, Sidoarjo. In implementing extension activities, there is a process of preparing activities starting from making proposals and submitting permits to related parties. As a form of evaluation, this activity was attended by 17 participants. Participants were very enthusiastic about taking part in the activity and 95% of the audience could understand the efforts to prevent dengue fever with 4M Plus